Game Media as the Fastest Brain Stimulus to Increase Children's Learning Capability - Erlina Sukmawati; Rahmat Mulyono (Risalah, Jurnal Pendidikan dan Studi Islam, 2023)
With the development of technology, education is required to be more advanced and modern to be able to keep pace with rapid technological developments. To be able to advance teacher education, they must begin to be open with more modern learning media, one of the learning media that needs to be developed is interactive multimedia based. The problem now is that teachers are not yet open to interactive multimedia-based learning media. The purpose of this study was to understand how simulation and game-based learning media affect students' learning comprehension in "Acid-Base" Chemistry learning at SMA Gotong Royong Semin Gunungkidul. The research was conducted with class X students in semester 2 of SMA Gotong Royong Semin, namely class XA (simulation-based learning media) as the control class and class XB (game-based learning media) as an experimental class with 40 students per class. The research method used is quasi-experimental. The chosen design is nonequivalent control group design. The sampling technique in this study used purposive sampling. Test the validity of the items based on the judgment of experts (judgment expert) and reliability test using Cronbach's Alpha. Data analysis techniques for testing research results used the normality test, homogeneity test, t test and Mann-Whitney test with data processing using the SPSS 17.0 program. The results of the study show that game-based learning media is better as a medium in conveying learning material in chemistry subjects for students' learning comprehension than simulation-based learning media. This is shown by the posttest hypothesis test. The results of the posttest hypothesis test with Mann-Whitney, the significance value is 0.00 <0.05, so Ho is rejected and Ha is accepted, which means that simulation-based learning media is different from game-based learning media as a medium in conveying learning material in chemistry subjects to student learning comprehension. In the descriptive analysis of the posttest data, it can be concluded that game media is better as a medium in conveying learning material in chemistry subjects for students' learning comprehension than simulation learning media.